(untitled) (Bangladesh Journal of Plant Taxonomy, 2023)
Fungal endophytes were isolated from the leaves, stems and roots of two widely used medicinal plantsviz.,Andrographis paniculata (Burm. f.) Wall. exNeesand Centella asiatica (L.)Urban. A total of 28 endophytic fungi were identified based on morphological and molecular analyses. The identified fungi were: Aspergillus flavus (Link), A. fumigatus (Fresen.), A. niger (Tiegh), A. terreus (Thom), Cladosporium sp., Colletotrichum sp., Curvularia chonburiensis (Tibpromma & K.D. Hyde), C. hominis (Da Cunha, Madrid, Gené & Cano), C. lunata (Wakker), C. lycopersici (Tandon & Kakkar), Curvularia sp., Fusarium falciforme (Carrión), F. phaseoli (Burkh.), F. solani (Mart.), F. udum (Berk.), Fusarium sp., Lasiodiplodia theobromae (Pat.), Monodictys paradoxa (Corda), M. putredinis (Wallr.), Penicillium commune (Thom), P. chrysogenum (Thom), P. oxalicum (Currie & Thom), Penicillium sp. 1, Penicillium sp. 2, Penicillium sp. 3, Penicillium sp. 4, Scytalidium lignicola (Pesante) and Talaromyces trachyspermus (Shear). Among them A. flavus, A. niger, A. terreus, Cladosporium sp., Colletotrichum sp. and Penicillium sp. 1 were isolated from both the plants. Curvularia chonburiensis, Curvularia hominis, Curvularia lycopersici, Fusarium falciforme, Fusarium phaseoli, Monodictys paradoxa, Penicillium commune and Scytalidium lignicola were found to be new records for Bangladesh. Findings of this study will be helpful for better understanding of endophytic fungal diversity and the species richness in those medicinal plants. Bangladesh J. Plant Taxon. 30(1): 111-122, 2023 (June)